Conservative or radical surgery for pediatric papillary thyroid carcinoma: A systematic review of the literature. Issue 10 (October 2015) - Jin, Xi; Masterson, Liam; Patel, Anant; Hook, Liz; Nicholson, James; Jefferies, Sarah; Gaze, Mark; Nassif, Ramez; Eller, Robert; Hulse, Tony; Jani, Piyush
Abstract Background Pediatric papillary thyroid carcinoma (PTC) is characterized by an aggressive clinical course. Early diagnosis is a challenge and treatment consists principally of partial or total thyroidectomy ± neck dissection and radioactive iodine therapy. Due to the rarity of PTC in children, there is no consensus on optimal surgical treatment. Methods and results A literature search was carried out using PubMed, Embase, Medline, Cochrane and Web of Science. Seven studies (489 patients) investigating the outcome of surgically managed pediatric PTC were identified. No clear advantage in survival or recurrence rate was found for total thyroidectomy compared to other surgical approaches. Conclusion Despite the aggressive behavior of PTC, prognosis is good, with low mortality. After removal of disease and prevention of recurrence, reduction of iatrogenic complications are a priority in this age group. Due to the paucity of available evidence, this review cannot recommend conservative or radical surgery for pediatric papillary thyroid carcinoma. To answer this question, we recommend the establishment of a randomized controlled trial with adequately matched baseline variables.